2016
DOI: 10.7717/peerj.2591
|View full text |Cite
|
Sign up to set email alerts
|

Pacing during an ultramarathon running event in hilly terrain

Abstract: PurposeThe dynamics of speed selection as a function of distance, or pacing, are used in recreational, competitive, and scientific research situations as an indirect measure of the psycho-physiological status of an individual. The purpose of this study was to determine pacing on level, uphill and downhill sections of participants in a long (>80 km) ultramarathon performed on trails in hilly terrain.MethodsFifteen ultramarathon runners competed in a  173 km event (five finished at  103 km) carrying a Global-Pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 23 publications
6
29
1
Order By: Relevance
“…Importantly, HP runners showed a more even pace with less speed variations than LP ones, perhaps indicating that a more conservative pacing strategy is the most appropriate to attain optimal performance in endurance events performed in extreme conditions. In contrast to previous ultramarathon studies (Kerherve et al, 2015(Kerherve et al, , 2016Renfree et al, 2016), but confirming others FIGURE 3 | Percentage of time spent at speeds corresponding to a substantial speed reduction (SSR <3.5 km·h −1 ), walking (from 3.5 to 5.9 km·h −1 ), walk-to-running transition (from 6.0 to 8.0 km·h −1 ) and running (>8.0 km·h −1 ). (A) HP vs. LP; (B) male vs. female; *, significant difference (P < 0.05) between performance levels or sexes in the same speed range; ‡, significant difference (P < 0.05) when compared to 3.5-5.9 km·h −1 LP; †, significant difference (P < 0.05) when compared to lower speed range(s) in the same performance level or sex; LP = low performance; HP, high performance.…”
Section: Discussionsupporting
confidence: 77%
“…Importantly, HP runners showed a more even pace with less speed variations than LP ones, perhaps indicating that a more conservative pacing strategy is the most appropriate to attain optimal performance in endurance events performed in extreme conditions. In contrast to previous ultramarathon studies (Kerherve et al, 2015(Kerherve et al, , 2016Renfree et al, 2016), but confirming others FIGURE 3 | Percentage of time spent at speeds corresponding to a substantial speed reduction (SSR <3.5 km·h −1 ), walking (from 3.5 to 5.9 km·h −1 ), walk-to-running transition (from 6.0 to 8.0 km·h −1 ) and running (>8.0 km·h −1 ). (A) HP vs. LP; (B) male vs. female; *, significant difference (P < 0.05) between performance levels or sexes in the same speed range; ‡, significant difference (P < 0.05) when compared to 3.5-5.9 km·h −1 LP; †, significant difference (P < 0.05) when compared to lower speed range(s) in the same performance level or sex; LP = low performance; HP, high performance.…”
Section: Discussionsupporting
confidence: 77%
“…This type of events is integrated with the natural environment, but affects the performance of the runners [41]. In mountainous areas, marathon races are in the level, uphill and downhill gradients due to the high ground undulations, so the runners' speed selection is also different from that of the flat race [15]. Studies have observed mountain super marathon run athlete the influence of the medial meniscus extrusion for people's health, and the results that mountain super marathon runner (without symptoms of knee joint, knee joint injury or surgery) observed under the limit load of the medial meniscus extrusion is a kind of temporary and reversible phenomenon, with the passage of time is completely reversible [24].…”
Section: Correlations Between Terrain/landforms and Marathon Eventsmentioning
confidence: 99%
“…When studying the risk identification of marathon events, Jun and Zhang identified environmental and natural risks [14]; the impact of different terrains on marathon runners' performance. The pace selection, the degree of slope and running speed of marathon runners on uphill and downhill sections are significantly correlated to their performances [15]; and altitude training that can improve the physiological functions of marathon runners and enhance their performance [12,16]. Indeed, research has found that marathon events are mostly distributed in spring (week 14 to 17) and autumn (week 41 to 44) and the average temperature of host cities varies close to optimal value for long distance races [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stage of competition, the possibility of time fastest qualification, start position, altitude, and the number of competitors per race have been identified as influencing factors in the adopted pacing behaviour [88]. Finally, it has been highlighted in several studies that the appropriate strategy in competition is obviously related to other external aspects such as terrain [79,[89][90][91][92], temperature [82,92], and humidity [82] rather than solely the other competitors.…”
Section: Time Trial Competitionsmentioning
confidence: 99%